THE CONDITION OF JOINTS DEFORMATION FOR ROAD BRIDGES - Kosiak, V. M.; Kovalchuk, V. V. (Science and Transport Progress, 2006)
The article makes analysis of the state of deformation joints in autoroute bridges and their influence on the general condition of the facilities, gives historic summary of the development of deformation joint constructions, formulated basic requirements to the present-day designs, and systematizes basic factors determining the choice of designs of deformation joints.